The role of leadership style in the relationship between organizational climate and burnout - Tunçay, Esra (My University, 2013)
Bu tez çalışmasının başlıca amacı kurum iklimi ve tükenmişlik arasında bir ilişki olup olmadığını tespit etmek ve eğitim çevrelerinde kurum iklimi ve tükenmişliğe etki eden faktörler üzerine kapsamlı bir çalışma yapmaktır. Çalışma ayrıca kurum iklimi ve tükenmişlik arasındaki ilişkide algılanan liderlik tarzlarının etkisini de araştırmayı hedeflemektedir. Bunun için, çeşitli liderlik tarzlarının önemli karakteristik özelliklerinin etkileri incelenmiştir. Araştırmada yer alan diğer liderlik tarzlarının arasında, hizmetkâr liderlik tarzının tükenmişlik üzerinde etkisi tespit edilmiştir. Veriler kesitsel araştırma yöntemiyle elde edilmiştir. Çalışmada, örneklem grubunu Türkiye’nin farklı üniversitelerinin

Hazırlık nda Okutman olarak görev alan 172 kişi oluşturmuştur. Elde edilen sonuçların özellikle hazırlık programlarının yöneticileri için faydalı sonuçlar sağlaması beklenmektedir. ABSTRACT The overall purpose of this thesis is to investigate whether there is an association between organizational climate and burnout, and to obtain an enhanced understanding of factors related to organizational climate and burnout in education environment. The research also aims to find out the effect of the perceived leadership style in the relationship between organizational climate and burnout. To do that, significant characteristics of numerous leadership styles are statistically tested to examine the effect of this relationship. Among the other leadership styles, servant leadership style is found to have a significant effect on burnout. The data are based on cross-sectional questionnaire studies. A sample of 172 Instructors of English Language working in English Language Preperatory Programs of universities in Turkey have been used in the study. Results revealed are expected to be beneficial especially for directors of the university preperatory programs.
Keywords: Örgütsel Bağlılık; Örgütsel Davranış; Tükenmişlik (Psikoloji); Yönetim